Physics Concept of High School Students in Northern Bone for Ad-vancing Songkok Recca Production - Martawijaya, M. A.; Hasyim, M.; Musniar, A.; Zharvan, V.; Taqwin, M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
This research aims to determine the physics conceptions of high school students in Northern Bone in developing the production of Songkok Recca using an alternative material, water hyacinth fiber. This qualitative study focuses on a descriptive case, which is the students' perceived lack of conception. The subjects used are four individuals interested in physics and are familiar with the process of making Songkok Recca. The case occurs in the students' school environment, which is also the production site of Songkok Recca. Data collection techniques in this research include observation, interviews, and documentation. The research data is analyzed through several stages, namely data collection, reduction, presentation, and data verification. Based on the research findings and discussions, it can be concluded that the students lack physics conceptions. They are only able to express some physics concepts, while some students are not familiar with those concepts.Based on the research results, it can be concluded that the students lack physics conceptions. They are only able to express some physics concepts, and some students are not familiar with those concepts. Water hyacinth fiber is deemed suitable as an alternative material for making Songkok Recca based on feasibility tests. The average tensile strength of wet water hyacinth fiber is 20.808,74021 N/m2, while the average tensile strength of dry water hyacinth fiber is 841.418,2808 N/m2.